Maqashid Al-Syari’ah Manajemen Pendidikan Islam di Indonesia - Muslimatun Rika Evania (Journal of Educational Management Research, 2022)
The object or scope of Islamic education is very broad, because it includes formal Islamic education (educational institutions), informal Islamic education (family education) and non-formal Islamic education (pesantren and ta'lim councils). This is the very fundamental and urgent point of difference between education management and Islamic education management. This difference requires managers to have the knowledge and skills to fully and comprehensively implement management values and processes into Islamic education. Islamic education is the process of guiding physically and spiritually based on Islamic laws towards the formation of the main personality according to Islamic norms or standards. This can be seen from the goals of Islamic law. Substantially the purpose of the Shari'a which we call "Maqashid al-Shari'ah" contains benefits. Based on the results of the study, Islam views management as a virtue (mashlahah) and that goodness is in line with the objectives of shari'ah (maqashid al-Shari'ah) namely the benefit of religion, soul, lineage, intellectual property, and of course property.